Caste discrimination and UN - Pinto, Ambrose (2002)
The United Nations Committee on Elimination of Racial Discrimination, concluding its discussion on descent-based discrimination,strongly condemned caste practice in South Asia. This describes a new framework for moving towards the elimination of caste-based, descent-based discrimination. - Reproduced.
Keywords: Racial discrimination; United Nations; Caste